Effect of mass distribution and collection angle in pulsed laser deposited films – a sampling method for chemical characterization of spent nuclear fuel. Issue 12 (5th October 2020) - Maity, U. K.; Manoravi, P.; Joseph, M.; Sivaraman, N.
Abstract : Effect of mass distribution and collection angle in PLD films from a single target having a wide mass range (24 to 238 amu). Abstract : Pulsed laser deposition (PLD) can be used as a sampling tool for chemical characterization of irradiated nuclear fuel when coupled with mass spectrometry analysis. The quantity of sample obtained by PLD is very small (typically a few nanograms), thereby reducing the radiation exposure to a considerable extent, but still provides the spatial profile of the irradiated pellet accurately (uncertainty error ∼1%) compared to the conventional gamma spectrometry method (error >5%), which is traditionally employed. Since PLD involves deposition of a laser ablated plume on a substrate, the mass distribution in such a plume has been studied at different angles with respect to the target normal at the plume center. The target used is a UO2 pellet mixed with different elements thereby covering a wide range of masses (24 to 238 amu). The PLD samples collected at different angles are dissolved in nitric acid and analyzed by inductively coupled plasma mass spectrometry (ICP-MS). The distribution patterns show systematic variation with respect to the angles of deposition, nature of the species (ion/neutral) in the laser produced plasma plume, mass number, ionization potential and sublimation energy of the species of interest. The results obtained are compared with the literature data and found to be in good agreement. Moreover, this study is the first report on mass distribution of a PLD based sample, covering such a wide mass range (24 to 238 amu) in a single target, and it also highlights the optimum collection angle (0 ± 12°) required for stoichiometric film deposition.